Beyond Old Boys' Clubs: Financial Analysts' Utilization of Professional Connections - DU, MENGQIAO; ZHANG, RACHEL XI (Journal of Accounting Research, 2026)
ABSTRACT Women often lack the opportunity to join exclusive social clubs, limiting the benefits they derive from their social networks. We investigate whether, when given the opportunity to interact with the right people in a professional setting, women gain greater advantages from these connections for career performance and advancement compared to men. Using a unique data set that documents when, where, and with whom financial analysts interact at investor conferences, we find that female analysts show greater improvement in earnings forecast accuracy than their male counterparts after interacting with a firm's executives. Further evidence suggests that female analysts overcome homophily in conference interactions with executives and that they sustain their gains, enhancing forecast accuracy for up to three years. In addition, both the capital and labor markets recognize women's superior gains from conference connections. Our findings suggest that women capitalize on professional connections, highlighting the importance of promoting structured networking opportunities for women in professional environments.